IJCM_176A: Prehypertension and its association with anthropometric indices among young adult Bank Employees of a city in coastal district of Andhra Pradesh-A cross-sectional study. - Hansdah Paran Mohan; Sujatha P.; Sridevi G.; Madhavi B. Devi (Wolters Kluwer Medknow Publications, 2024)
Background: Hypertension is a rapidly emerging modifiable lifestyle disease and is often called as the silent killer. Owing to a steady increase in the prevalence it is of public health concern. Hypertension develops gradually preceded by prehypertension as evidenced by longitudinal studies. Bank employees lead a sedentary and highly stressful life that often leads to developing NCD's such as hypertension. The study aims to assess the prevalence of prehypertension among them. Objectives: 1. To assess the prevalence of Prehypertension among bank employees. 2. To determine the association between various anthropometric measurements and Prehypertension among bank employees. Methodology: A Cross-sectional Study was carried out among the bank employees of urban Kakinada, during October & November 2023 and their hypertension status was assessed. List of banks in the city was obtained and 32 of them were selected by simple random sampling using lottery method. Sample size was calculated using the formula=z2pq/l2 with an allowable error of 15% of prevalence.Prevalence(55.3%) was taken from the study done by Sira Jam Munira and sample size was 140.Young adults(25-44years) of age from the rank of Clerk and above were included in the study. Modified WHO STEPS questionnaire was used to collect data using Kobo toolbox and the data was analysed using MS Excel 2019 and SPSS 21. Prior approval was taken from Institutional Ethics Committee. Results: A total of 308 respondents constituted the study population. The mean age of the participants was 52.80±10.97 years. Among various domains of QOL, mean scores were found to be maximum for environmental domain (54.08± 14.76). Females have lower scores among various QOL domains as compared to their male counterparts. Age was found to be independent predictor for all the domains of QOL. Literacy, monthly family income, presence of self-reported stress and duration of the diabetes were all significantly associated with majority of domains of QOL on multivariate analysis (P<0.05). Conclusion: Advancing age and duration of diabetes were found to be among important predictors of QOL. Conclusion: Young adult bank employees had high prevalence of prehypertension and it was more prevalent among females.